2017
DOI: 10.14218/jcth.2016.00061
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Nonalcoholic Fatty Liver Disease: An Overview of Present and Future Therapies

Abstract: Nonalcoholic fatty liver disease (NAFLD) represents a major public health epidemic. Pharmacologic therapies for this condition are scarce, but multiple agents with novel mechanisms of action are in development. Here we review the pathophysiology and natural history of NALFD, diagnostic testing and data for currently available treatment strategies. We then turn our attention to promising developmental drugs and their respective trials. As the prevalence of fatty liver disease increases, clinicians will have mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 89 publications
0
13
0
1
Order By: Relevance
“…Collectively, these findings point toward oxidative stress as an important acting factor in the development in HFD‐dependent liver steatosis and establishment of a pro‐inflammatory state, which can further increase in NASH to progress into fibrosis and cirrhosis . Hence, abrogation of hepatic steatosis by combined DHA and HT would represent a crucial therapeutic strategy eluding disease progression into stages lacking efficacious handling at present time …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings point toward oxidative stress as an important acting factor in the development in HFD‐dependent liver steatosis and establishment of a pro‐inflammatory state, which can further increase in NASH to progress into fibrosis and cirrhosis . Hence, abrogation of hepatic steatosis by combined DHA and HT would represent a crucial therapeutic strategy eluding disease progression into stages lacking efficacious handling at present time …”
Section: Discussionmentioning
confidence: 99%
“…70,71 Hence, abrogation of hepatic steatosis by combined DHA and HT would represent a crucial therapeutic strategy eluding disease progression into stages lacking efficacious handling at present time. [4][5][6]…”
Section: Liver Molecular Changes Associated Withmentioning
confidence: 99%
“…The use of metformin to prevent progressive liver injury in NAFLD/NASH has been heavily debated . Many studies have shown an improvement in liver enzymes while taking metformin, but effects on histological endpoints have been less convincing .…”
Section: Discussionmentioning
confidence: 99%
“…Estresse oxidativo, inflamação hepática, disfunção mitocondrial, citocinas próinflamatórias desequilibradas, fibrose, resistência à insulina, hiperinsulinemia, ácidos graxos livres plasmáticos, fígado gorduroso e lesão de hepatócitos são condições que apoiam o desenvolvimento da esteato-hepatite gordurosa não alcoólica e fibrogênese. [8][9][10][11] A disfunção do tecido adiposo em doença hepática gordurosa não alcoólica tem sido associada a redução do catabolismo de aminoácidos de cadeia ramificada (BCAA) e ácidos graxos. Essa alteração está inversamente relacionada aos teores séricos de BCAA e de conteúdo hepático de gordura.…”
Section: Fisiopatologiaunclassified